2.75. Wiadomo, że: b) d) f) (sqrt(3) – 2)/(sqrt(3) + 2) – 12/(sqrt(3)) 1/(3 + sqrt(6)) + 1/(3 – sqrt(6)) (sqrt(6) – sqrt(3))/(sqrt(6) + sqrt(3)) – (sqrt(3) + sqrt(6))/(sqrt(3) – sqrt(6)) a) a ^ 2 + b ^ 2 = 25 oraz ab = 12 Oblicz (a – b) ^ 2 oraz |a + b| . b) a ^ 2 + b ^ 2 = 13c oraz (a + b) ^ 2 = 225 Oblicz ab oraz (a – b) ^ 2 . c) a ^ 2 – b ^ 2 = 36 oraz 7 – b = 2 . Oblicz a + b oraz aib. d) (a + b) ^ 2 = 225 , (a – b) ^ 2 = 121 oraz a > b . Oblicz ab oraz a ^ 2 – b ^ 2 . Potęga o wykładniku całkowitym ujemnym

2.75. Wiadomo, że: b) d) f) (sqrt(3) – 2)/(sqrt(3) + 2) – 12/(sqrt(3)) 1/(3 + sqrt(6)) + 1/(3 – sqrt(6)) (sqrt(6) – sqrt(3))/(sqrt(6) + sqrt(3)) – (sqrt(3) + sqrt(6))/(sqrt(3) – sqrt(6)) a) a ^ 2 + b ^ 2 = 25 oraz ab = 12 Oblicz (a – b) ^ 2 oraz |a + b| . b) a ^ 2 + b ^ 2 = 13c oraz (a + b) ^ 2 = 225 Oblicz ab oraz (a – b) ^ 2 . c) a ^ 2 – b ^ 2 = 36 oraz 7 – b = 2 . Oblicz a + b oraz aib. d) (a + b) ^ 2 = 225 , (a – b) ^ 2 = 121 oraz a > b . Oblicz ab oraz a ^ 2 – b ^ 2 . Potęga o wykładniku całkowitym ujemnym